New Liberal Arts Talents’ Cultivation in China: A Systematic Review - Liu, Yunhang; Rasul, Mohamad Sattar; Kamaruzaman, Fathiyah Mohd (Journal of Posthumanism, 2025)
New liberal arts (NLA) construction has gradually become a strategic choice for higher education to meet the technological revolution and global competition. Previous studies have been carried out to highlight the importance of NLA skills and strategies for talents’ cultivation in general, nevertheless, the study of the specification or attributes of NLA skills and strategies for talents’ cultivation are still limited. In this paper, the core collection of Web of Science (WOS), Scopus, and CNKI are used as data sources, and the literature related to NLA skills and strategies that have been carried out by previous researchers within year 2018 until 2023 are respectively used as research objects. The study employed Systematic Literature Review (SLR) and Preferred Reporting Items for Systematic Review Meta-Analyses (PRISMA) 2020 checklist to ensure a comprehensive and rigorous analysis of the available literature. By synthesising and analysing the findings from the final selected 13 articles, the constructs of NLA skills and strategies for NLA talents’ cultivation are explored. Finally, a framework of 7 NLA skills can be proposed and 5 innovative strategies are identified to be used as a reference to stakeholders to cultivate NLA talents based on the specification.